Efektivitas POC Daun Kirinyuh (Chromolaena odorata) Terhadap Pertumbuhan Dan Hasil Tanaman Jagung Pulut - Lindri Tangibali; Ayudhi Fajar Lintin; Adewidar Marano Pata’dungan; Willy Yavet Tandirerung (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aimed to evaluate the effectiveness of liquid organic fertilizer (POC) derived from kirinyuh (Chromolaena odorata) leaves on the growth and yield of potted corn plants. The research was carried out at the Agricultural Development Center (BPP) of Malimbong Balepe’, Tana Toraja District, South Sulawesi Province, located at an altitude of 815 meters above sea level. The experiment was designed using a simple randomized block design (RBD) consisting of four treatments: K0 = control (without treatment), K1 = 20% concentration of kirinyuh leaf POC (200 ml POC + 800 ml water), K2 = 40% concentration of kirinyuh leaf POC (400 ml POC + 600 ml water), and K3 = 60% concentration of kirinyuh leaf POC (600 ml POC + 400 ml water). Parameters observed included plant height at 5 and 7 weeks after planting (WAP), number of leaves at 7 WAP, ear length, ear diameter, and ear weight per plant. The results showed that kirinyuh leaf POC significantly affected the growth and productivity of potted corn plants. Application of POC at 60% concentration (K3) produced the best results, indicated by increased plant height, greater number of leaves, longer ear length, larger ear diameter, and higher ear weight compared to other treatments and control. This finding suggests that kirinyuh leaves, which are often considered as agricultural weeds, have potential as an alternative source of organic fertilizer that is environmentally friendly, low-cost, and effective in improving crop growth and yield. In conclusion, kirinyuh leaf-based liquid organic fertilizer, particularly at a concentration of 60%, demonstrated the highest effectiveness in supporting corn growth and productivity. These results provide practical insights for farmers to utilize locally available organic materials as an alternative to chemical fertilizers in sustainable agricultural practices.